KOMPETISI PEMILIHAN MODA ANGKUTAN PENUMPANG BERDASARKAN MODEL LOGIT-BINOMIAL-SELISIH DAN LOGIT-BINOMIAL-NISBAH - Dwi Novi Wulansari (Jurusan Teknik Sipil Universitas Bangka Belitung, 2016)
In the urban transport system, need to observe the behavior of road users in order to know the factors that affect in an election mode. In order to obtain a model that can explain the mode choice probability of the user in choosing public transport modes, as well as be able to estimate the sensitivity of user in determining the mode choice when to amend an attribute journey. This study was performed using a discrete choice analysis on the behavior of individuals. The model used is the mode choice logit-binomial-difference models and logit-binomial-ratio models.The selection of two modes being simulated is 1) Airports Train and Bus Damri, 2) Airport train and taxi, 3) Airport train and private vehicles (cars). Based on the results of the sensitivity analysis, it is known that the most sensitive influence modal choice probability is travel costs. Where changes in the cost of the trip will result in a change mode choice probability is relatively higher than when there is a change on other attributes.